Design and experimental analysis for a high-power wireless charging system design for electric vehicles - Ayoade, Idowu Adetona; Longe, Omowunmi Mary (Frontiers in Future Transportation, 2026)
Wireless electric vehicle (EV) charging systems enhance user convenience and are fundamental to realising autonomous and contactless mobility. Nevertheless, efficiency at high power levels remains constrained by coil misalignment, magnetic leakage, and switching losses. This study presents the design of an analytical hypothesis model formulated to relate the coupling coefficient, mutual inductance, and load conditions to achieve power transfer. The model is then simulated and experimentally validated through a 5 kW at 85 kHz inductive power transfer (IPT) system employing a series–series compensated resonant topology. The mutual inductance coupling and the efficiency (k2Q1Q2) were developed to quantify the sensitivity of power transfer to variations in air gap and misalignment, as well as the quality factor, Q1,Q2. The proposed system achieved a peak simulated efficiency of 92.5% and a measured wall-to-battery efficiency of 88.4%, with harmonic distortion below 6.5% and stable soft-switching operation across the 85–88 kHz range. The experimental prototype maintained zero-voltage switching (ZVS), precise DC-link voltage regulation (310 ± 2 V), and stable constant-current/constant-voltage (CC–CV) battery charging for a 72 V, 40 Ah lithium-ion pack. Power loss analysis indicated that coil copper losses increased from 6.2% at nominal alignment to 10.5% under a 60 mm lateral offset, while inverter and rectifier losses accounted for 4.1% and 3.0%, respectively. Efficiency decreased from 5.02 kW (92.5%) at 10 mm air gap to 3.8 kW (86.7%) at 60 mm, validating the predicted dependence on coupling coefficient and mutual inductance (M≈25μH). Magnetic field mapping confirmed emissions below the ICNIRP 27 µT limit at 10 cm, ensuring user safety. Simulation and experimental results demonstrated strong alignment, confirming effective harmonic mitigation, robust inverter modulation, and accurate CC–CV control. The system’s validated performance, analytical model, and experimental results collectively verify the design’s robustness, safety, and scalability, meeting SAE J2954 standards and offering a high-efficiency solution for next-generation residential and light-commercial EV charging applications.